Risk Tolerance: The Influence of Gender and Life Satisfaction - Dickason-Koekemoer, Zandri; FerreiraSuné (Journal of Economics and Behavioral Studies, 2019)
Abstract: Financial managers base an investor’s risk profile on their demographics and level of risk investors are willing to tolerate. Risk tolerance is often influenced by the different levels of life satisfaction that an investor experience and may differ based on the demographic composition of that investor. Demographic variables such as gender can differentiate between investors level of life satisfaction, which can ultimately affect investment decisions. As a result, the degree of life satisfaction can affect investment decisions by manipulating the level of risk that investors are willing to tolerate. Male and female investors can be categorised into different risk tolerance levels based on their satisfaction with life status. The aim of this study is to determine the risk tolerance level of male and female investors considering their level of life satisfaction. The results of this study indicated that the more unsatisfied investors are with their lives the less likely they will be to take on high-risk investments. Therefore, low life satisfaction is accompanied by a low-risk tolerance level. Male investors had higher life satisfaction compared to female investors. Female investors were only willing to tolerate high risk when experiencing extremely low life satisfaction or extremely high life satisfaction stages.